LAW ENFORCEMENT FOR DEVELOPMENT ACTIVITIES IN THE COASTAL AREAS OF KUPANG - Johana Art Cindy Peny; Jimmy Pello; Umbu Lily Pekuwali (Jurnal Dinamika Hukum, 2016)
Coastal zone is a crucial zone because it has a wealth of natural resources of high economic value while at the same time is prone to adverse affects due to interference of development activities. This research is an empirical legal research which examines that there have been various local regulations with which management of the zone must comply but within those regulations themselves there exist contradictory articles. Furthermore,  this research discovered that this was caused by the drafting of local regulations do not consider to environmental aspects in coastal  zone, inaccuracy in the process of local regulations drafting and the strong ego sector so that the Government issued building license by law enforcement officials that deviate much from the existing regulations. The incompliance of which was done for the sake of economic gain without the least consideration about the environmental aspects and proper land use whereas the development in coastal zone should have a strong regulatory foundation and not based on interests of public authority and sheer power. Keywords: Development Activities, Land Use, Coastal zone